2015
DOI: 10.1080/15548627.2015.1051295
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic adaptations in diabetic cardiomyopathy differ between type 1 and type 2 diabetes

Abstract: Abbreviations: AMPK, AMP-activated protein kinase; CTSD, cathepsin D; DM, diabetes mellitus; GFP, green fluorescent protein; HBA1c, glycated hemoglobin a 1; MAP1LC3/LC3, microtubule-associated protein 1 light chain 3; LV, left ventricular; MTOR, mechanistic target of rapamycin; SIRT1, sirtuin 1; Mn-SOD, superoxide dismutase 2, mitochondrial; STZ, streptozotocin; SQSTM1/p62, sequestosome 1.Little is known about the association between autophagy and diabetic cardiomyopathy. Also unknown are possible distinguishi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
168
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(180 citation statements)
references
References 49 publications
7
168
0
Order By: Relevance
“…Another recent study claimed an increased autophagy in STZ diabetic mouse hearts as shown by increased LC3-II levels and GFP-LC3 puncta. However, chloroquine treatment reduced rather than further increased the LC3-II levels[129], suggesting that cardiac autophagic flux was actually inhibited. Cardiac autophagy is also reduced in several forms of metabolic syndrome and type 2 diabetic animal models[127129], but it is not as consistent since other studies reported either increased[130] or unchanged autophagy in the type 2 diabetic hearts[127, 128].…”
Section: Autophagy and Mitophagy In The Diabetic Heartmentioning
confidence: 99%
See 1 more Smart Citation
“…Another recent study claimed an increased autophagy in STZ diabetic mouse hearts as shown by increased LC3-II levels and GFP-LC3 puncta. However, chloroquine treatment reduced rather than further increased the LC3-II levels[129], suggesting that cardiac autophagic flux was actually inhibited. Cardiac autophagy is also reduced in several forms of metabolic syndrome and type 2 diabetic animal models[127129], but it is not as consistent since other studies reported either increased[130] or unchanged autophagy in the type 2 diabetic hearts[127, 128].…”
Section: Autophagy and Mitophagy In The Diabetic Heartmentioning
confidence: 99%
“…However, chloroquine treatment reduced rather than further increased the LC3-II levels[129], suggesting that cardiac autophagic flux was actually inhibited. Cardiac autophagy is also reduced in several forms of metabolic syndrome and type 2 diabetic animal models[127129], but it is not as consistent since other studies reported either increased[130] or unchanged autophagy in the type 2 diabetic hearts[127, 128]. These different conclusions could be attributed partly to the fact that not all studies have followed the suggested guidelines to determine autophagic flux [84, 85].…”
Section: Autophagy and Mitophagy In The Diabetic Heartmentioning
confidence: 99%
“…Thus, inhibition of autophagy through Rheb overexpression and mTORC1 activation in the heart increased infarct size following ischemia [16], suggesting a protective role. Similarly, enhancement of autophagy using resveratrol restored cardiac diastolic function, while inhibition of autophagy using chloroquine worsened both cardiac diastolic and systolic function in leptin receptor-deficient ( db/db ) mice [39]. Furthermore, autophagy insufficiency occurs in sustained cardiac hypertrophy as seen in chronic left ventricular hypertrophy and recent reports suggest that improving autophagy could alleviate cardiac hypertrophy [47].…”
Section: Discussionmentioning
confidence: 99%
“…In support of the contention that autophagy plays a beneficial role in the diabetic heart, studies have shown that activation of autophagy via fenofibrate, 132 metformin, 123, 133 ghrelin, 134 or resveratrol, 135 rescues diabetes-induced cardiac dysfunction; and inhibition of autophagy via chloroquine 135 exacerbates diabetes-induced diastolic dysfunction. In contrast, other studies have shown that autophagy may play a detrimental role in the diabetic heart: inhibition of autophagy via Epigallocatechin-3-gallate, 136 chloroquine, 137 global Beclin1 haploinsufficiency 127 or global Atg16L deficiency 127 rescues diabetes-induced cardiac pathology.…”
Section: Cardiopathology Involvementmentioning
confidence: 99%